THE UNDERCURRENT INDONESIA’S CITY GAS SECTOR WITH THE MODERATING WORK FORCES - Andry Prima; Havidh Pramadika; Mustamina Maulani; Arinda Ristawati; Wiwik Dahani; Prana Ugiana Gio (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2022)
The continues dynamics as the object of observation in studying the milestones that any company or industry should consistently achieve in long-term growth expected to be stable. The same applies to the natural gas distribution sector or known as city gas. The movement of data from year to year continues to depict an increasing trend with regard to the city gas sector in Indonesia. The objective of this particular study is to provide a better understanding of the city gas distribution sector in Indonesia and to provide a clearer picture of a number of latent variables that must be accommodated to optimize the distribution of natural gas to cities in Indonesia. The methodology used in this study is the Structured Equation Method (SEM). In a more specific description, path analysis developed from multivariate regression is used to analyze the correlation between indicators and latent variables so as to determine the validity of the multiple regression model. Still related to the research method, by sorting the data collection released from the Indonesian Central Statistics Agency and grouping data from indicators of city gas distribution companies during the period 2010-2020 divided into income, number of workers, wages, the volume of city gas distributed, and costs associated with operations. The results of this work are to provide input to the authorities and other stakeholders in order to optimize the growth of Indonesia's gas distribution sector. The value or originality of this study is to reveal the impact of latent variables that have the status of moderating variables. Study limitations - Due to the inaccessibility of non-disclosure primary data and limited data availability, it is assumed that the data obtained from the Indonesian Central Statistics Agency is valid to describe the explanatory variables of the city gas distribution sector in Indonesia.